Sistem Informasi Manajemen Penerimaan Karyawan Berbasis Computer Assisted Test - Ditavia Dara Fadila; Siti Sufaidah; Moh Anshori Aris Widya (KH. A. Wahab Hasbullah University, 2021)
Employee recruitment that occurs at PT. Shoei Surabaya, which is located in Mojoagung district, still uses manual methods in the process of hiring new employees. So that it is appropriate to develop a computer-based employee recruitment management information system that helps support tests for HRD staff or for those who will apply for jobs to come and provide information without having to go directly to the company. In this study, a design plan using the waterfall system development method aims to make the new employee recruitment process usable according to the company's needs. So that with the construction of an employee admission information system based on this computer-assisted test, you can immediately find out information about job vacancies without having to come to the company first and supervise the costs that must be paid properly from the company or applicant.